2022
DOI: 10.3390/atmos13081263
|View full text |Cite
|
Sign up to set email alerts
|

Health Exposure Assessment of Firefighters Caused by PAHs in PM4 and TSP after Firefighting Operations

Abstract: Among the many different chemicals in the air, polycyclic aromatic hydrocarbons (PAHs) pose a serious threat to human health. Firefighters are exposed to them both during fire suppression and in fire vehicles and fire stations due to inhalation of the fumes from contaminated clothing and personal protective equipment. This study aimed to estimate the exposure and cancer risk caused by suspended particulate matter and PAHs present in these particles. Air samples were collected for 4 months in a garage of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
0
0
1
Order By: Relevance
“…So far, limited studies focusing on firefighters' health-risk analysis are available in the literature. Rakowska et al [125] demonstrated the existence of carcinogenic and non-carcinogenic risks associated with Polish firefighters' exposure to fire emissions in the garage of the fire station after the day of a firefighting operation (1.01 × 10 −4 -3.45 × 10 −4 and 0.12-0.57, respectively); carcinogenic-risk values were up to 100 times higher than the levels estimated in this study. Similar results were reported by Valdenaire and co-authors [126] for Parisian sapper firefighters, with an estimated carcinogenic risk level varying between 2.25 × 10 −5 and 1.16 × 10 −4 .…”
Section: Firefighter's Health Risk Evaluationcontrasting
confidence: 60%
“…So far, limited studies focusing on firefighters' health-risk analysis are available in the literature. Rakowska et al [125] demonstrated the existence of carcinogenic and non-carcinogenic risks associated with Polish firefighters' exposure to fire emissions in the garage of the fire station after the day of a firefighting operation (1.01 × 10 −4 -3.45 × 10 −4 and 0.12-0.57, respectively); carcinogenic-risk values were up to 100 times higher than the levels estimated in this study. Similar results were reported by Valdenaire and co-authors [126] for Parisian sapper firefighters, with an estimated carcinogenic risk level varying between 2.25 × 10 −5 and 1.16 × 10 −4 .…”
Section: Firefighter's Health Risk Evaluationcontrasting
confidence: 60%